Examining Factors Influencing Consumers Intention and Usage of Digital Banking: Evidence from Indonesian Digital Banking Customers - Rila Anggraeni; Raditha Hapsari; Noor Awanis Muslim (APMBA (Asia Pacific Management and Business Application), 2021)
This paper aims to analyze important factors influencing the intention and use of digital banking as perceived by consumers of the Indonesia commercial bank. This paper adopts variables in the unified theory of acceptance and use of technology 2 (UTAUT 2). The data was collected by distributing questionnaires to the 281 respondents by employed purposive sampling technique. To assessing the acceptance model, a structural equation approach based on Partial Least Squares (SEM-PLS) was used. The UTAUT2 model was proved adequate to explain digital banking behavior intention and usage. The findings demonstrated that habit is the highest variable that determines the behavioral intention and use behavior. Hedonic motivation and social influence also predict intention. Indonesia has a collectivist culture, which emphasizes the high value of the group, so opinions and information from others will affect people's intentions and actions. Surprisingly, effort expectancy, facilitating conditions, performance expectancy, and price value do not have a significant relationship which some possible reasons were explained further. In this article, practical impication also discussed.